Analysis of the Impact of Decreasing the Width of Direct Stairs in Apartments on RSET for All Occupants in Korea - et. al., Sang Im Lee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study analyzed the RSETs for 11-story or less apartments where the building-related laws were not retroactively applied, with consideration of the decrease of direct stairs width due to obstacles piled up on the direct stairs. The RSET was shown to be 631.8 seconds when the width of the direct stairs was 1,260mm. The evacuation time exceeded 5 minutes even when there were no obstacles due to the delayed evacuation start time. The risk increased when the width of the direct stairs was decreased to 960mm, 760mm, and 560mm because of obstacles, and the RSETs were 768.8 seconds, 803.3 seconds, and 834.4 seconds respectively. There are various ways to eliminate the occurrence of obstacles on direct stairs which increase RSET : First, it is necessary to remove the exception that permits the placement of obstacles on the stairs. Second, penalties for the placement of obstacles on the direct stairs should be enforced as written. Third, the fire safety managers need the authority to act on behalf of the fire officials. Lastly, it is necessary to encourage residents to report instances of obstacle accumulation. Henceforth, more research is needed on the spread speed of smoke and toxic gases depending on whether fire doors are installed through fire simulation.